A regular analogue of Smilansky model. Issue 1 (December 2014) - Exner, Pavel
Abstract In this note we review several recent results describing a two‐dimensional Schrödinger operator with a potential unbounded from below which can be understood as a regular version of Smilansky model. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)